Sistem Informasi Akademik Sma Negeri 3 Putra Bangsa Lhoksukon Berbasis Web - Iskandar Zulkarnaini (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2021)
This research aims to find out the needs of information systems, the development of academic information systems, academic information system performance and the implementation of Information Systems at Sma Negeri 3 Putra Bangsa Lhoksukon to help the performance of teachers and employees in improving the quality of services. The method used in this research is the research and development method. The data collection technique in this study uses questionnaires and interviews. Data analysis techniques are performed using quantitative descriptive analysis techniques. This research was conducted at Sma Negeri 3 Putra Bangsa Lhoksukon by involving teachers and employees as research subjects. The results showed that: Schools need an information system that is able to accommodate all school data. Information Systems developed in the form of Academic Information Systems. The system has eight main menus, namely teacher data, student data, employee data, school inventory, correspondence, lesson schedules, schedules, teachers and room dawal. The development of information systems through four stages, namely needs analysis, design, coding and testing. Academic Information System performance testing that has been developed gets a rating percentage of 86.81%. The value shows that the information system that has been developed is very good and worth using. The development of the Academic Information System of Sma Negeri 3 Putra Bangsa Lhoksukon is highly approved because it affects the quality of school services. This is evidenced by the 86.33% percentage of system functionality testing. So it can be concluded that the Academic Information System at Sma Negeri 3 Putra Bangsa Lhoksukon that has been developed is worth using